A State of Art Review: Volatile Organic Compounds and Periodontitis - Ghasemirad, Mohammad; Tavakol, Omid; Etesami, Soroush; Nikeghbal, Kiana; Nikeghbal, Dorsa; Abedi Diznab, Fatemeh; Mahmoudi Anzabi, Reza (Galen Medical Journal, 2024)
Background: Periodontitis is a notable public health issue impacting more than 1 billion individuals globally, and its connection with volatile organic compounds (VOCs) has attracted growing interest. This review seeks to explore the existing knowledge on the link between VOCs and periodontitis. Materials and Methods: An extensive literature review was performed to pinpoint key VOCs associated with periodontitis. Results: The review revealed that several VOCs, such as hydrogen sulfide, methanethiol, indole, limonene, formaldehyde, 1,4-dichlorobenzene, 2-Aminothiazoline-4-carboxylic acid, ethyl acetate, methyl mercaptan, dimethyl sulfide, acetone, pyridine, picolines, o-xylene, mandelic acid, and N-acetyl-S-(4-hydroxy-2-butenyl)-L-cysteine, are linked to periodontitis, with some contributing to heightened oral infection, direct tissue harm, oral malodor, and inflammatory responses, while the causality of this phenomenon remains unclear as it is uncertain which event occurs first. Conclusion: This review enumerates the VOCs that may either contribute to or arise from periodontitis; hydrogen sulfide appears to be the most extensively studied VOC in the context of periodontitis. This review highlights the intricate relationship between VOCs and periodontitis and underscores the necessity for additional research to clarify the mechanisms underlying this association and to guide the creation of effective prevention and treatment strategies.